2017
DOI: 10.1021/acs.jpca.7b10189
|View full text |Cite
|
Sign up to set email alerts
|

NMR Chemical Shift of a Helium Atom as a Probe for Electronic Structure of FH, F, (FHF), and FH2+

Abstract: In this work, we present the first results of outer electronic shell visualization by using a He atom as a probe particle. As model objects we have chosen F, FH, and FH species, as well as the hydrogen-bonded complex FH···F at various H···F distances (3.0, 2.5, 2.0, and 1.5 Å and equilibrium at ca. 1.14 Å). The interaction energy of investigated objects with helium atom (CCSD/aug-cc-pVTZ) and helium atom chemical shift (B3LYP/pcS-2) surfaces were calculated, and their topological analysis was performed. For co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…Thus, it can be concluded, that for nitrogen-containing species, similarly to fluorine-containing ones, [11] there is a correlation between maximal values of |MESP| Analysis of dependencies presented in Figure 5 for oxygen containing species (5) and (6) mation for the studied set of electroneutral molecules. However, [42] it was shown that in case of anion F − and cation FH 2 + MESP extrema are missing, while r 2 δ He retains its features. We hope that this finding could be extrapolated to larger sets of molecules with localized LPs, at least to molecules similar to the ones studied here.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, it can be concluded, that for nitrogen-containing species, similarly to fluorine-containing ones, [11] there is a correlation between maximal values of |MESP| Analysis of dependencies presented in Figure 5 for oxygen containing species (5) and (6) mation for the studied set of electroneutral molecules. However, [42] it was shown that in case of anion F − and cation FH 2 + MESP extrema are missing, while r 2 δ He retains its features. We hope that this finding could be extrapolated to larger sets of molecules with localized LPs, at least to molecules similar to the ones studied here.…”
Section: Resultsmentioning
confidence: 97%
“…In other words, MESP and ∇ 2 δ He give qualitatively comparable information for the studied set of electroneutral molecules. However, it was shown that in case of anion F − and cation FH 2 + MESP extrema are missing, while ∇ 2 δ He retains its features. We hope that this finding could be extrapolated to larger sets of molecules with localized LPs, at least to molecules similar to the ones studied here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations